Analisis Penyelesaian Kredit Bermasalah melalui Rescheduling untuk meningkatkan Profitabilitas pada Masa Pandemi Covid-19 Pada Koperrasi Simpan Pinjam dan Pembiayaan (KSPPS) Cisaat - Yesi Rahmawati; Nor Norisanti; Faizal Mulia Z (Journal of Economic, Bussines and Accounting (COSTING), 2022)
Sharia Savings and Loans Cooperative (KSPPS) Cisaat is a company engaged in the financial sector, namely in financing or Sharia-based fund and savings capital. The reserach research was triggered by the problem encountered by the company, namely the inability of the debtors to fulfill their obligations to the company. The research was aimed at determining the settlement of non-performing loans through rescheduling as well as the level of profitability and the factors causing the occurrence of non-performing loans in the company. The population of the research were the financial statements generated from the management’s accounting activities at KSPPS Cisaat, while the sample used was a recap of Portfolio At Risk (PAR) for the period of 2020. The research deployed descriptive analysis method with quantitative approach and carried out data collection techniques, namely observation, interviews, literature study and documentation. The techniques of analyzing data applied were Portfolio At Risk (PAR) analysis, Return On Assets (ROA), and horizontal analysis technique. Based on the result of the research, it shows that the criteria for non-performing loans are included in the very risky category due to the inability of members to fulfill their obligations. Thus, factors causing non-performing loans are internal factors, namely weak credit analysis, debtor character, family conflict, smooth running of business, third person in community organization, as well as external factor in terms of the Covid-19 pandemic in 2020, with the implementation of rescheduling repayments of non-performing loans reaching 90% are declared settled, and the company's profitability level increasing every month. Keywords:Non-Performing Loans, Rescheduling, Profitability Level